GENOMIC DNA EXTRACTION METHOD FROM MATURE LEAF OF LAI (Durio kutejensis Becc.) - Fitri Handayani; Rani Agustina Wulandari; Rudi Hari Murti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
Lai (Durio kutejensis Becc.) is an indigeneous germplasm of Kalimantan which has some superiorities compared to its close-relative, durian (Durio zibethinus Murr.). Genetic exploration of lai is important to support its breeding program. According to rapid development in molecular biology, genetic exploration effort of lai will be easier. One of significant step in any molecular biology activities is DNA isolation to produce high quality DNA for further analysis. Leaves of lai, as other perennial crop, contain of high concen-tration of polysaccharides and polyphenol which will be co-extracted with the DNA. These compounds can interfere enzymes activities in subsequent molecular analysis. The aim of this study was to establish an optimal and effective DNA extraction method to obtain high-quality DNA from mature leaf of lai. An established extraction buffer and its modification were used in this study. The result showed that modification 4 could produce high quality DNA, and was considered to be the most effective DNA extraction method for mature leaf of lai.